HEALED FRACTURE OF RABBIT FEMUR POST IMPLANTATION WITH DEMINERALIZED GRAFT MATERIAL OF BALI CATTLE BONE POWDER - Asih, Ni Putu Trisna; Wirata, I Wayan; Sudimartini, Luh Made; Winaya, Ida Bagus Oka; Kardena, I Made; Gorda, I Wayan (Buletin Veteriner Udayana, 2019)
The purpose of this study to determine the microscopic changes in rabbit femur fracture healing post-implantation of the graft material demineralized powder bone of bali cattle. Twelve local male rabbits were divided into two groups randomly. Group A consisted of three rabbits used as a control, in which the diaphysis rabbit femur bones were drilled with a diameter of 5mm and depth of drill to reach the medulla, without giving graft material. Group B nine rabbits that were drilled the same as group A and given a powder bone graft. Monitoring progress of bone healing was done in a row against one rabbits in group A and group B three rabbits at week 2 nd , 4 th , and 6 th post-surgery with biopsy for sampling bone subsequently prepared to see microscopic changes the bone with using hematoxylin-eosin (HE) staining. The results showed that the group B bone healing observ by reducing inflammation, proliferation of fibrolast, osteoblasts, osteoclasts, osteocytes, woven bone, trabecular bone, and neovascularization. In conclusion, the origin of the bone graft material bali cattle was able to induce the healing process of bone fractures in rabbits.